Answer:
<h2><u><em>
a²+2ab+b²-c²</em></u></h2>
Step-by-step explanation:
Solve:
(a+b+c) (a+b-c)=
(a²+ab-ac+ab+b²-bc+ac+bc-c²)=
a²+ab-ac+ab+b²-bc+ac+bc-c²=
a²+2ab+0ac+b²+0bc-c²=
a²+2ab+b²-c²
Answer:
Sorry I cant help But I think that well I dont know but if you have any other questions i can help you with I can.
Step-by-step explanation:
Answer:
B
Step-by-step explanation:
The sum of the 3 angles in a triangle = 180°, thus
p = 180° - (80 + 20)° = 180° - 100° = 80° and
q = 180° - (45 + 55)° = 180° - 100° = 80°
Thus p = q → B
Word form-five hundred six thousand,seven hundred nine
Expanded form-500,000+6,000+700+9
Answer:
1/2
Step-by-step explanation:
I think so im not sure tho so sorry if its incorrect